1998
DOI: 10.1099/0022-1317-79-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Infection with classical swine fever virus: effects on phenotype and immune responsiveness of porcine T lymphocytes.

Abstract: T lymphocytes obtained from pigs infected with a lethal dose of classical swine fever virus were analysed for phenotypic changes in the composition of T-cell subpopulations and for alterations in their immune responsiveness in vitro during the course of disease. Viral antigen detected in all subpopulations and the selective depletion of CD4 N CD8 N γ/δ T cells showed that peripheral blood T lymphocytes were affected in the terminal stage (14-19 days postinfection) of classical swine fever whereas no implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 33 publications
0
43
1
Order By: Relevance
“…50 Considerable functional alterations of T lymphocytes have been demonstrated in CSF. 36,47,48 B cells are therefore deprived of the protection they would otherwise enjoy during the course of the disease, which may aggravate the apoptosis observed in B cells in the spleen during CSF.…”
Section: Discussionmentioning
confidence: 99%
“…50 Considerable functional alterations of T lymphocytes have been demonstrated in CSF. 36,47,48 B cells are therefore deprived of the protection they would otherwise enjoy during the course of the disease, which may aggravate the apoptosis observed in B cells in the spleen during CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Here further replication takes place and the virus is spread via blood to secondary replication sites such as spleen, bone marrow, and visceral lymph nodes [133,134,135]. Apoptotic reactions as well as phagocytic and secretory activation can be observed in several macrophage populations [136,137,138,139,140,141,142,143,144]. These activated macrophages seem to play a crucial role in (immuno-)pathogenesis while direct damage by the virus could be almost excluded for many lesions occurring in the course of CSFV infection.…”
Section: Pathogenesis and Immune Responsesmentioning
confidence: 99%
“…Depletion of peripheral B and T lymphocytes, with a preferential B lymphocyte deficiency in the circulatory system as well as in lymphoid tissues, has been described during CSFV infection (Susa et al, 1992;Summerfield et al, 1998a). A decrease in T lymphocyte activity (Pauly et al, 1998) and regressive changes in lymphoid organs during CSF (Summerfield et al, 2000(Summerfield et al, , 2001Sánchez-Cordó n et al, 2002 have also been observed. Inhibition of both cellular and antibody responses are therefore observed after CSFV infection.…”
Section: Introductionmentioning
confidence: 90%